A 7-metoxiflavona apresenta efeito tocolítico por modulação negativa da via Rho cinase e da calmodulina em ratas - Brasileiro, Laiz Aline Silva (2018)
Since the 7-methoxyflavone flavonoid (7-MF), one of the major components isolated from Zornia brasiliensis Vogel, showed in vitro tocolytic effect in rats, it was decided to characterize this mechanism. The rat uterus was placed in baths for isolated organ where isotonic and isometric contractions were monitored (n = 5). It was observed that 7-MF relaxed the pre-contracted rat uterus by both oxytocin (OCI) (EC50 = 3.5 ± 0.3 x 10-5 M) and KCl (EC50 = 2.2 ± 0.2 x 10-5 M) being about 2 times more potent compared to this contractile agent, suggesting a participation of voltage-dependent calcium channels (CaV) in tocolytic effect of 7-MF. To confirm this hypothesis, cumulative curves to CaCl2 were performed in the absence and presence of 7-MF and a shift of the control curve to the right was observed, with a reduction of maximum effect only at the concentration of 3 x 10-5 M (30%), indicating that probably blocking Ca2+ influx through CaV is not the main tocolytic mechanism of flavonoid. It was decided to evaluate a possible participation of the potassium channels in tocolytic effect of 7-MF using cesium chloride, a non-selective K+ channel blocker, and in this presence control curve of 7-MF relaxation was not deviated (EC50 = 3.3 ± 0.6 × 10-5 M ), discarding positive modulation of the K+ channels in tocolytic effect of 7-MF. Once prostaglandins are involved in physiopathological uterine processes and the inhibitors of cyclooxygenase (COXs) are one of the main classes used for the treatment of dysmenorrhea so, it was decided to evaluate the possible involvement of the COXs pathway in the tocolytic mechanism of 7-MF and it was observed that in the presence of indomethacin, a nonselective COXs inhibitor, the control curve was not displaced (EC50 = 4.8 ± 0.6 x 10-5 M), indicating that the inhibition of these enzymes are not involved in the tocolytic effect of 7-MF. Another pathway of smooth muscle relaxation is adrenergic-β receptors. In order to evaluate a possible activation of these in the action of 7-MF, used (S)-(-)-propranolol, a adrenergic-β receptor antagonist, was used and it was observed that there was no change in the relaxing potency in the presence of the blocker (EC50 = 2.2 ± 0.5 x 10-5 M), indicating that 7-MF does not act by positive modulation of these receptors to induce the tocolytic effect. As a major route of relaxation of the smooth muscle is the nitric oxide (NO) pathway, it was decided to evaluate the participation of this pathway in the tocolytic effect of 7-MF and it was observed that in the presence of L-NAME, a non-selective inhibitor of NO synthase (NOS), there was no change in the relaxing potency (EC50 = 4.4 ± 1.2 x 10-5 M), also discarding this pathway in tocolytic effect of 7-MF. A common downstream step of the Gs and NO pathways is the enzyme phosphodiesterase (PDE). In the presence of aminophylline, a non-selective PDE, it was observed that there was no change in the relaxing potency of 7-MF (EC50 = 2.8 ± 0.5 x 10-5 M) indicating that it is probably not by its activation that the flavonoid exerts its tocolytic effect. Inhibition of contractile pathways can also lead to smooth muscle relaxation, thus the RhoA/Rho kinase pathway (ROCK) participation in the tocolytic effect of 7-MF was evaluated. In the presence of Y-27632, a non-selective ROCK blocker, the curve was shifted to the left, with an increase in the relaxation potency around 22 times (EC50 = 1.6 ± 0.7 x 10-6 M) suggesting that 7-MF negatively modulates the RhoA/ROCK pathway to exert its tocolytic effect. Still in the contractile mechanism, calmodulin is one of the main mediators for Ca2+ signaling. In order to evaluate its participation in the tocolytic effect of 7-MF used calmidazolium, a calmodulin blocker, and was observed a potentiation of the relaxing effect of 7-MF (EC50 = 6.5 ± 1.6 x 10-7 M), around 54 times, confirming negative modulation of calmodulina in tocolytic effect. Thus, the mechanism of tocolytic action proposed for 7-MF in rats is the inhibition of the ROCK pathway and calmodulin.